Fungsi Manajemen Dalam Metode Dakwah - Erwan Efendi; Gusti Bayu Wiranda; Siti Wandari (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
The management function is the first step in carrying out all activities, especially in preaching, when a da'i / subject of proselytizing wants to do his proselytizing then he must first think or foresee to see the opportunities that occur before a definite plan is made. After doing the forecasting, the subject of proselytizing will draw up a plan such as, making material suitable for the object of proselytizing, so that his proselytizing can be accepted and understood correctly. After that organizing, this is beneficial for proselytizing because in this function a proselytizing manager carries out the entire process of grouping people, dividing the duties of each proselytizing subject, preparing the media to be used, and being responsible for his work to achieve predetermined goals. And after carrying out the organization, the culmination for a proselytizing subject is to enter the community / object of proselytizing to do his proselytizing which has been carefully prepared in advance. And the last step in the management function is to evaluate the results of the proselytizing that has been carried out, in order to correct the mistakes that arise and correct so that the proselytizing becomes even better.